Hubungan Antara Tingkat Pengetahuan Dan Konsumsi Softdrink Dengan Status Gizi Remaja Di SMP Muhammadiyah 10 Surakarta - KURNIAWAN, Sidiq, Susi Dyah Puspowati, M.Si, Dyah Widowati, SKM (2015)
Background: Problems with nutritional status can lead to emotional and social problems for adolescents. The nutritional status of school children is important to note because the consumption patterns of children in school are not monitored by their parents. Knowledge is one of the factors that can affect the nutritional status in adolescents although indirectly. Consumption of soft drinks excessive amounts of lead in soft drinks excess calories are converted into fat form. Purpose: To know correlation between the level of knowledge and softdrink consumption with teens nutritional status in Muhammadiyah 10 junior high school Surakarta Method of the Research: The research implemented a survey-observational with cross-sectional approach. Subject of the research is 45 individuals selected by using simple random sampling. Data of knowledge and soft drink consumption was taken by used a recall form, data of antropometri was taken by used body mass index. Data is analyzed by using correlation test of Rank Spearman. Result: Based on univariate analysis, most of the research subjects have a good knowledge about the softdrink is equal to 62.2%, most of the research subjects rarely consume soft drinks is equal to 80% and most of the energy contributed by softdrink for students enough that is equal to 84.4%, most of the study subjects had normal nutritional status that is equal to 55.6%. The results of Rank Spearman correlation test for knowledge and nutritional status p value = 0.403, softdrink consumption and nutritional status p value = 0.040, energy contributed by softdrink and nutritional status p value = 0.026. Conclusion: There had been correlation between sofdrink consumption frequency and the energy contribution with nutritional status. There had not correlation between knowledge with nutritional status